Cation-Induced Transcriptional Regulation of the dlt Operon of Staphylococcus aureus - Koprivnjak, Tomaz (American Society for Microbiology, 2006)
Lipoteichoic and wall teichoic acids (TA) are highly anionic cell envelope-associated polymers containing repeating polyglycerol/ribitol phosphate moieties. Substitution of TA with d-alanine is important for modulation of many cell envelope-dependent processes, such as activity of autolytic enzymes, binding of divalent cations, and susceptibility to innate host defenses. d-Alanylation of TA is diminished when bacteria are grown in medium containing increased NaCl concentrations, but the effects of increased salt concentration on expression of the dlt operon encoding proteins mediating d-alanylation of TA are unknown. We demonstrate that Staphylococcus aureus transcriptionally represses dlt expression in response to high concentrations of Na(+) and moderate concentrations of Mg(2+) and Ca(2+) but not sucrose. Changes in dlt mRNA are induced within 15 min and sustained for several generations of growth. Mg(2+)-induced dlt repression depends on the ArlSR two-component system. Northern blotting, reverse transcription-PCR, and SMART-RACE analyses suggest that the dlt transcript begins 250 bp upstream of the dltA start codon and includes an open reading frame immediately upstream of dltA. Chloramphenicol transacetylase transcriptional fusions indicate that a region encompassing the 171 to 325 bp upstream of dltA is required for expression and Mg(2+)-induced repression of the dlt operon in S. aureus.